#TITLE_ALTERNATIVE# - ANDIKA (NIM : 10105092); Dosen Pembimbing : Dr. Marcus Wono Setya Budhi, IRANDA
In a seismic processes, the term "migration" is related to spatial data correction which is used to describe accurately a refector position. One of the migration technique that can be used is finite difference migration methods. Finite difference method using the equation as an approximate wave equation which can be used to migrate stacked data from zero offset time to migrated time where is the wavefield. In this paper, we will attempt to use this method on a few velocity model.